2006
DOI: 10.1007/s00436-006-0262-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Neospora caninum and Toxoplasma gondii in domestic cats from Brazil

Abstract: The occurrence of antibodies to Neospora caninum and Toxoplasma gondii was determined in 400 domestic cats (Siamese, Persian, and undetermined breeds) from the Municipality of Araçatuba, Sao Paulo, Brazil, through the indirect fluorescence antibody test (IFAT). Of the 400 cats, 100 were seropositive to T. gondii (25%, titer > or =64) and 98 to N. caninum (24.5%, titer > or =16). The rate of seropositive cats for T. gondii was correlated with age (chi(2)=35.7; p<0.001), with a higher number of infected animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
13
3
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 29 publications
8
13
3
4
Order By: Relevance
“…However, future studies are sorely needed to elucidate the real role of L. infantum in the epidemiology of N. caninum and T. gondii in cats. A positive correlation between the presence of N. caninum and T. gondii antibodies was also found in the present study, which corroborates the findings of previous studies, due to the feeding habits of cats (FRENKEL, 1973;HUANG et al, 2004;BRESCIANI et al, 2007). Recently, several authors reported that small birds and rodents living in synanthropic areas could act as intermediate hosts for T.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, future studies are sorely needed to elucidate the real role of L. infantum in the epidemiology of N. caninum and T. gondii in cats. A positive correlation between the presence of N. caninum and T. gondii antibodies was also found in the present study, which corroborates the findings of previous studies, due to the feeding habits of cats (FRENKEL, 1973;HUANG et al, 2004;BRESCIANI et al, 2007). Recently, several authors reported that small birds and rodents living in synanthropic areas could act as intermediate hosts for T.…”
Section: Discussionsupporting
confidence: 93%
“…There are few reports about the occurrence of N. caninum in cats. In this study, we found a seroprevalence to N. caninum of 22.5%, which is similar to previous reports in cats in the states of São Paulo (24.5%) and Maranhão in Brazil (27%) (BRESCIANI et al, 2007;BRAGA et al, 2012), and in Italy (24.8%) (FERROGLIO et al, 2005), but higher than that found by Dubey et al (2002) among cats sampled in the cities of São Paulo and Guarulhos, Brazil (11.9%). The possibility of crossreactions between T. gondii and N. caninum are remote, because cross-reactivity is observed only when soluble antigens are used, while surface antigens such as those used in IFA usually do not cause cross-reactions (DUBEY et al, 1996;HIGA et al, 2000).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although there were only a small number of seropositive animals, these observations suggest that those categories would not represent risk factors for T. gondii and that all cats are equally exposed to infection. Similar findings were obtained by Bresciani et al (2007), Coelho et al (2011) andCardia et al (2013), in cats from Brazil. Nevertheless, seroprevalence of infection in domestic cats has been found to vary with their lifestyle (wild, stray or domestic), age, serological test used and geographical location (Gauss et al, 2003).…”
Section: Discussionsupporting
confidence: 88%